Misuse of Enduring Powers of Attorney - Kent, Rachel (Victoria University of Wellington Law Review, 2003)
This paper critically evaluates the Law Commission’s recommendations as presented in the Commission’s report reviewing Part IV of the Protection of Personal Property Rights Act 1988. This legislation defines the scope for enduring powers of attorney (EPAs). The paper advocates that the establishment of a central register for EPAs will be of substantial benefit, as it will provide an effective means of monitoring the use and misuse of EPAs. The paper concentrates on the effects of the current regime on older people, and it interviews six individuals who are actively engaged in work with older people in the Wellington region to identify the main areas of concern surrounding EPAs. The focus of the interviews was developed from the Law Commission’s recommendations against the establishment of a central register. The paper identifies some very real concerns with the current law's ability to curb the misuse of EPAs which leave older people open to abuse. It concludes that the Law Commission needs to re-evaluate the issue of misuse of EPAs as its report does not adequately deal with current flaws in the law.